Rancang Bangun Alat Pelapis Kaset Sebagai Upaya Pencegahan Infeksi pada Pemeriksaan Radiografi - Prastanti, Agustina Dwi; Darmini, Darmini; Daryati, Siti; Wibowo, Gatot Murti; Suan, Kesita Grace Natalia (Jurnal Imejing Diagnostik (JImeD), 2025)
Background: Infection control in radiography is carried out by wrapping tapes and radiograph equipment using polyethylene plastic bags. Existing conditions in the hospital require at least 1 to 2 layers of plastic for each radiography in patients with a history of infectious diseases. The use of plastic causes the amount of infectious plastic waste to be increased. Therefore, an alternative is needed to use acrylic mica material that can be used repeatedly and is environmentally friendly as a replacement for plastic bags.Methods: This research design is a Research and Development (RnD) study with the ADDIE model which is carried out with five stages, namely analysis, design, development, implementation, and evaluation. The data collection method is carried out by observation, testing the function of the tool, and then the data is processed and analyzed by criticizing the results of radiographic image quality using ImageJ software.Results: Four sizes of precision radiographic cassette coating have been produced with four radiographic cassette sizes. The average decrease in the mean number is 1.07%.Conclusion: The radiograph quality from using acrylic mica cassette coatings in radiograph examinations can still produce good quality radiographs based on the results of histogram graph analysis which produces graphs that have a similar shape between those without using cassette coatings and those with cassette coatings.